Surgical versus balloon valvotomy in neonates and infants: results from the UK National Audit. Issue 1 (14th February 2019) - Dorobantu, Dan Mihai; Taliotis, Demetris; Tulloh, Robert Michael; Sharabiani, Mansour Thagavi Azar; Mohamed Ahmed, Eltayeb; Angelini, Gianni Davide; Stoica, Serban Constantin
Abstract : Objective: There are conflicting data on choosing balloon aortic valvoplasty (BAV) or surgical aortic valvotomy (SAV) in neonates and infants requiring intervention for aortic valve stenosis. We aim to report the outcome of both techniques based on results from the UK national registry. Methods: This is a retrospective study, including all patients under 1 year undergoing BAV/SAV between 2000 and 2012. A modulated renewal approach was used to examine the effect of reinterventions on outcomes. Results: A total of 647 patients (488 BAV, 159 SAV, 292 neonates) undergoing 888 aortic valve procedures were included, with a median age of 40 days. Unadjusted survival at 10 years was 90.6% after initial BAV and 84.9% after initial SAV. Unadjusted aortic valve replacement (AVR) rate at 10 years was 78% after initial BAV and 80.3% after initial SAV. Initial BAV and SAV had comparable outcomes at 10 years when adjusted by covariates (p>0.4). AVR rates were higher after BAV and SAV reinterventions compared with initial valvoplasty without reinterventions (reference BAV, HR=3 and 3.8, respectively, p<0.001). Neonates accounted for 29/35 of early deaths after the initial procedure, without significant differences between BAV and SAV, with all late outcomes being worse compared with infants (p<0.005). Conclusions: In a group of consecutive neonates and infants, BAV and SAV had comparable survival and freedom from reintervention as initial procedures and when performed as reinterventions. These findings support a treatment choice based on patient characteristics and centre expertise, and further research into the best patient profile for each choice.